RPGR is a guanine nucleotide exchange factor for the small GTPase RAB37 required for retinal function via autophagy regulation - Ruhong Ying; Cong Li; Huirong Li; Juan Zou; Mengxin Hu; Qiang Hong; Yin Shen; Ling Hou; Hanhua Cheng; Rongjia Zhou (Cell Reports, 2024)
Summary: Although the small GTPase RAB37 acts as an organizer of autophagosome biogenesis, the upstream regulatory mechanism of autophagy via guanosine diphosphate (GDP)-guanosine triphosphate (GTP) exchange in maintaining retinal function has not been determined. We found that retinitis pigmentosa GTPase regulator (RPGR) is a guanine nucleotide exchange factor that activates RAB37 by accelerating GDP-to-GTP exchange. RPGR directly interacts with RAB37 via the RPGR-RCC1-like domain to promote autophagy through stimulating exchange. Rpgr knockout (KO) in mice leads to photoreceptor degeneration owing to autophagy impairment in the retina. Notably, the retinopathy phenotypes of Rpgr KO retinas are rescued by the adeno-associated virus-mediated transfer of pre-trans-splicing molecules, which produce normal Rpgr mRNAs via trans-splicing in the Rpgr KO retinas. This rescue upregulates autophagy through the re-expression of RPGR in KO retinas to accelerate GDP-to-GTP exchange; thus, retinal homeostasis reverts to normal. Taken together, these findings provide an important missing link for coordinating RAB37 GDP-GTP exchange via the RPGR and retinal homeostasis by autophagy regulation.